Utility of microRNAs in Exhaled Breath Condensate as Diagnostic Biomarkers to Differentiate Pulmonary Sarcoidosis from Pulmonary Tuberculosis - Rai, Divyanjali; PP, Adwika; Tak, Jaya; Bangaru, Sunil; Pattnaik, Bijay; Yadav, Sunita; Kumari, Seetu; Kumari, Jyoti; verma, Umashankar; Yadav, Geetika; Dhaliwal, RS; Bhatraju, Naveen; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Pulmonary sarcoidosis and pulmonary tuberculosis (PTB) are two granulomatous diseases with similar clinical presentations. This study explored the potential of microRNAs (miRNAs) in exhaled breath condensate (EBC) as non-invasive diagnostic biomarkers to distinguish between pulmonary sarcoidosis and PTB. Methods: EBC samples were collected from 46 participants (20 with PTB, 26 with pulmonary sarcoidosis) and 20 healthy controls and miRNA profiling was done. Differentially expressed miRNAs were further validated using qRT-PCR in independent cohorts in EBC (17 PTB, 18 sarcoidosis, and 25 controls) and blood (10 PTB, 10 sarcoidosis, and 10 controls). Results: Initial profiling identified 19 miRNAs differentially expressed between pulmonary sarcoidosis and PTB, one between sarcoidosis and controls, and 22 between PTB and controls. The top five upregulated miRNAs (miR-132, miR-362-5p, miR-181c, miR-181a, and miR-512-3p) and two downregulated miRNAs (miR-454 and miR-139-5p) in sarcoidosis compared to PTB were selected for validation. Validation showed significant downregulation (p value